Praktik Jasa Laundry Chesta Barelejo Madiun Perspektif Hukum Islam - Siti Fatimah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2020)
This is a of field research to highlight on